Tradisi Kemaliq dan Perang Topat sebagai Strategi Membangun Perdamaian yang Tangguh dan Replikatif di Indonesia: Kemaliq and Perang Topat Traditions as Recillient and Replicatable Peacebuilding Strategies in Indonesia - Spastyono, Jeko; Malik, Ichsan; Wahyudi, Bambang; Widodo, Pujo (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2023)
Cultures may either flourish or decline based on different situations. Due to its dynamicity, utilizing cultural values as a foundation for peace or peacebuilding is generally deemed an unwise investment for governments. Nevertheless, in this study, we challenge this notion with unique cultural peace values exhibited by tradition of Kemaliq and Perang Topat in Lombok Island, Indonesia. By employing qualitative methods, we delve into the cultures and highlighting their exceptional qualities that differentiate them from other peace-making cultural efforts. We found distinctively that these traditions' greatest strengths lie in their primary activities of sharing of sacred sites between Islamic and Hindu adherents in Kemaliq, and the enthusiastic act of channeling all grievances into the thrown topat towards the opposing side in Perang Topat. With the peacemaking power of both lying on their material activities, rather than in abstract values that may be subject to change or erosion over time, making them durable, replicate-able, and dynamically usable peace cultures, much different than their counterparts. Accordingly, we highly recommend that, especially, the government of Indonesia to invest in promoting these traditions as valuable sources of local and even national peacemaking endeavors.